Neonatal lupus erythematosus. - Lepore, L.; Pennesi, M.; Longo, F.; Ciana, G. (European Journal of Pediatric Dermatology, 2018)
A newborn girl with lupus erythematosus was reported. Antibodies anti U 1-RNP were detected both in the mother and in the newborn girl, whereas anti-Ro anti-bodies were not present. The pathogenesis of neonatal lupus erythematosus was also discussed with regard to the role played by anti-Ro/La and anti-U1-RNP antibodies and to the possible prevention.